Correction of Midline Deviation and Unilateral Crossbite Treated with Fixed Appliance - Domenico Ciavarella; Marta Maci; Laura Guida; Angela Pia Cazzolla; Eleonora Lo Muzio; Michele Tepedino (Hindawi Limited, 2023)
The following case report describes the treatment of a 20-year-old man with dental and facial asymmetry. Patient presented upper dental midline shifted 3 mm to right side and the lower one 1 mm to left side, skeletal class I, molar class I and canine class III on the right side, molar class I and canine class II on the left side, and upper and lower crowding on teeth #12, #15, #22, #24, #34, and #35 in crossbite. The treatment plan provided four extractions: in the superior arch the right second and the left first premolar and in the lower arch first premolars on the left and right sides. Wire-fixed orthodontic device was used in combinations with coils to correct the midline deviation and to close post-extractive spaces, avoiding miniscrew implants. At the end of the treatment, optimal functional and aesthetic results were obtained: realignment of the midline improved facial symmetry, correction of the crossbite on both sides, and a good occlusal relationship.